The road of green transition in China - Huang, Haifeng; Siddiqui, Asif (My University, 2013)
Topics: the "Chinese dream", China’s approach to economic development, the 21st century: policy meets framework , the road ahead.
Presented on December 15, 2013 at the 2013 International Conference on Strategic Management: Strategy in Emerging Markets: Management, Finance and Sustainable Development held at the University of Sichuan in Chengdu, China.
Keywords: economic development; China